18F-Fluorocholine PET/MRI in Restaging of Prostatic Carcinoma in Relation to PSA Level and Detection of Active Disease - Ferda, Jiří; Ferdová, Eva; Baxa, Jan; Fínek, Jindřich; Topolčan, Ondřej (Anticancer research, 2018)
AIM: To evaluate our own experience with 18F- fluoromethylcholine-(FCH)-positron-emission tomography combined with magnetic resonance imaging (PET/MRI) in restaging of patients with prostatic carcinoma and elevated serum prostate-specific antigen (PSA) level. PATIENTS AND METHODS: The analysis was performed on a sample of 100 male patients who underwent 18F-FCH-PET/MRI, with a mean age of 63.2 years (range=47-78 years). The imaging was performed using an integrated PET/MRI hybrid system after intravenous application of 18F-FCH at a dose of 1.25 MBq/kg. The number and sites of pathological accumulation of FCH related to local recurrence, nodal spread and skeletal metastases were compared to corresponding MRI findings; furthermore, the relation of PSA level and presence of FCH accumulation in tumorous tissue was assessed; finally we correlated the findings of different sites of metastatic involvement. RESULTS: In patients with a PSA level up to 2 ng/ml, accumulation in tumorous tissue of local recurrence or metastases was found in 83.33% in cases of biochemical relapse, and in patients with PSA level above 5 ng/ml in 100% of cases. In general, we found any finding explained rise of PSA level in 94% of patients. CONCLUSION: 18F-FCH-PET/MRI using an integrated system with 1,25 MBq/kg dosing of FCH is a valuable tool in evaluation of restaging in patients with prostatic carcinoma, with high detection rate even in those with a low serum PSA level.
Keywords: Prostatic carcinoma; Prostatic Neoplasms; Adenocarcinoma; Magnetic Resonance Imaging; nádory prostaty; magnetická rezonanční tomografie; Humans; lidé středního věku; Choline; Fluorine Radioisotopes; restaging; Aged; fluoromethylcholine; Prostate-Specific Antigen; senioři; lidé; PSA; cholin; PET/MRI; multimodální zobrazování; staging nádorů; Male; Middle Aged; prostatický specifický antigen; Positron-Emission Tomography; adenokarcinom; Neoplasm Staging; mužské pohlaví; radiofarmaka; pozitronová emisní tomografie; radioizotopy fluoru; Multimodal Imaging; Radiopharmaceuticals